Do larger school grants improve educational attainment? Evidence from urban Mexico. Issue 4 (2nd October 2021) - Araujo, M. Caridad; Martinez, M. Adelaida; Martinez, Sebastian; Perez, Michelle; Sanchez, Mario
ABSTRACT: We study the effects of larger cash grants on the educational attainment of low-income middle and high school students in Mexico. Starting in 2009, school grants from the Oportunidades conditional cash transfer programme increased by 27 percent for females and 30 percent for males in 263 of 551 urban localities. Using a difference-in-difference analysis of longitudinal programme registries linked to national standardised tests, we find that students with larger grants experienced lower dropout rates in middle school and were more likely to graduate from high school on time. Specifically, the likelihood of graduation increased by 38.7 percent for females and 41.3 percent for males, suggesting an elastic response to the larger grants.